Efeito do 4-etilfenol sobre o crescimento e capacidade fermentativa da linhagem industrial de Saccharomyces cerevisiae PE-2 - Covre, Elizabete Aparecida (2019)
One of the main contaminating yeasts of ethanol production in Brazil is the species Dekkera bruxellensis. It is able to produce volatile phenolic compounds such as 4-vinylphenol and 4-ethylphenol from hydroxycinnamic acids present in wine grapes due to the action of the enzymes hydroxycinnamate decarboxylase and vinyl phenol reductase. Hydroxycinnamic acids are also present in sugarcane juice and molasses and thus volatile phenols could be synthesized during ethanolic fermentation. The effects of the presence of 4-ethylphenol and the interaction with factors related to the ethanol production and its implications on Saccharomyces cerevisiae are not yet well established. This work evaluated the effects of the addition of 4-ethylphenol on the growth of an industrial strain of S. cerevisiae (PE-2) under the influence of pH, ethanol and sucrose concentration, an on its fermentative capacity. By using the central compound rotational design (CCRD), the effect of the variables 4-ethylphenol, pH, ethanol and sucrose concentration on the maximum specific growth rate of S. cerevisiae was evaluated in microplate experiments in YPS medium (yeast extract-peptone-sucrose), at 30oC. Following, single-cycle fermentations lasting 12h in YPS medium, pH 4.5, 17% sucrose, at 30oC, with 4-ethylphenol in concentrations of 10 and 20 mg/L being added at the start or after 4h of fermentation, were carried out. Values of 15 mg/L, 6%, 17% and 4.0 for 4-ethylphenol, ethanol, sucrose and pH, respectively, negatively influenced the maximum specific growth rate of S. cerevisiae. It was observed that the effect of 4-ethylphenol concentration was linked to the ethanol concentration in the medium and that 4-ethylphenol is capable of influencing S. cerevisiae growth when the concentrations of the other parameters are not suitable for the yeast viability.The addition of 4-ethylphenol on fermentation resulted in a significant effect on the number of yeasts, pH and alcohol content of the fermentation medium, resulting in a decrease in the fermentative efficiency. Therefore, it was concluded that the industrial yeast S. cerevisiae PE-2 growth and fermentative capacity are affected by the presence of 4-ethylphenol, a metabolite produced by D. bruxellensis, which may contribute to explain the impact of this yeast on bioethanol industrial production.